2016
DOI: 10.1155/2016/1529703
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Sequestration in Tropical and Subtropical Plant Species in Collaborative and Community Forests of Nepal

Abstract: Different plant species have different capacity of carbon sequestration but it is not assessed yet in Nepal. Therefore, this study was done to assess the species-wise carbon sequestration in two periods in forests. Three collaborative and three community forests were selected for the study. The selected forests were surveyed using GPS and mapped and stratified into tree, pole, and regeneration. Specifically 32, 33, and 31 samples were collected from Banke-Maraha, Tuteshwarnath, and Gadhanta-Bardibash collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 14 publications
3
18
0
1
Order By: Relevance
“…The variation of carbon stock across different species in this study shows that different plant species have different capacity to sequestrate carbon during photosynthesis supporting the findings in [32]. Although in this study we have used the generalized allometric equations to quantify carbon stock for all the thirty-three species, interestingly, the computed values of carbon in our study area are within that reported in other studies like [9,25,73,65], but they are contrary to the values reported in [32]. These contradicting findings might result from variation of species , location, age of the tree and methods of quantifying carbon stocks [32].…”
Section: Carbon Stock Across Different Speciessupporting
confidence: 88%
See 3 more Smart Citations
“…The variation of carbon stock across different species in this study shows that different plant species have different capacity to sequestrate carbon during photosynthesis supporting the findings in [32]. Although in this study we have used the generalized allometric equations to quantify carbon stock for all the thirty-three species, interestingly, the computed values of carbon in our study area are within that reported in other studies like [9,25,73,65], but they are contrary to the values reported in [32]. These contradicting findings might result from variation of species , location, age of the tree and methods of quantifying carbon stocks [32].…”
Section: Carbon Stock Across Different Speciessupporting
confidence: 88%
“…Carbon loss in forests ecosystems are the outcomes of anthropogenic activities [8,25]. Deforestation and degradation of terrestrial forest ecosystems are the main factors for the loss of carbon in the tropical forests [25,31,32]. Deforestation, degradation, and poor forest management reduce the capacity of forests ecosystems to store carbon [33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besarnya serapan karbon melalui pertumbuhan dan akumulasi biomassa ditentukan oleh sifat pertumbuhan, kondisi lahan, serta kecocokan antara jenis yang dikembangkan dengan kondisi lahan pengembangannya (Mandal, Jha, Dutta, Thapa, & Karmacharya, 2016). Krasikarpa merupakan salah satu jenis yang dipilih untuk ditanam pada lahan basah, baik pada tipe lahan endapan liat (marine clay) maupun lahan gambut, karena jenis ini tergolong jenis cepat tumbuh dan adaptif pada lahan basah.…”
Section: B Pembahasanunclassified